Implementasi Metode Scrum Agile Dalam Perancangan Sistem Informasi Tiketing Peribadatan Gereja Katolik Santo Barnabas Pamulang - Nikolaus Nisef Fo’era’era Zebua; Alvino Octaviano (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
At this time the implementation of mass at the church of Santo Barnabas Pamulang is still limited by following the health protocol (prokes). To avoid crowds and limit participants, a mass registration system has been created through the website. Therefore, all Saint Barnabas devotees who wish to attend mass offline are required to send data on family members and vaccine certificates to church officials through their respective ward administrators. With this system in effect, it is difficult for people who come from outside the area who live temporarily and do not have an environment or are visiting to be able to attend Mass. Web-based registration system specifically for participants that will be designed using the Agile Scrum method. With this system in place, people from outside the church area of St. Barnabas can continue to attend mass by registering online. It is hoped that this system can help church administrators in serving people who want to mass at the church of St. Barnabas, especially people who come from outside the area of Saint Barnabas.